The relationship between swimming speed and exhalation pattern in the breast stroke - Hara, H.; Onodera, S.; Watanabe, R.; Shibata, Y. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Breathing while swimming is one of the very important factors for swimming skills. Well-trained swimmers lift their faces to inspire air for as short a time as possible. To shorten breathing time, they exhale while their faces are still under water. They perform these motions, together with other leg and arm motions, unconsciously. This is the most skillful point of swimming for breathing near the water surface.